Guilielmia Weise, a little known Afrotropical flea beetle genus: systematic affinities and description of a second new species from Central Africa (Coleoptera, Chrysomelidae, Galerucinae, Alticini) - Biondi, Maurizio; D’alessandro, Paola (Zootaxa, 2017)
The genus Guilielmia Weise from the high mountains of Central Africa, known on a female specimen only, is redescribed based on new specimens of the type species, and the new species Guilielmia leleupi sp. nov. described here. Habitus photos, and microscope and scanning electron micrographs of diagnostic characters, including the aedeagus, are provided for both the species. Some considerations about taxonomic affinities and morphological adaptations to high altitudes are suggested.